2020
DOI: 10.1093/iwc/iwaa014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Meaningful Participation and the Situated Use of Technology in Community Music for Active Ageing

Abstract: An unfortunate tendency in previous HCI research has been to give the impression that it aims to ‘fix the problem’ of human ageing, suggesting a ‘deficit’ model of ageing or a ‘prosthetic’ model of technology. We conducted diary-aided interviews to investigate how technology use is situated in active, healthy older adults’ meaningful participation in community music. We argue that recognizing community music practices and technology use as situated action provides opportunities to grasp the subtleties of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…The rst type focuses on technology learning that is supported by the physical and social environment, for example, a community formed by OA to learn technology from each other at a designated physical meeting point (36). The second type focuses on social interaction that is supported by the physical environment and technology, for instance, a community for sharing, learning and managing music using technology where people can also meet at a designated physical location (37). The third type focuses on physical activity that is supported by the social environment and technology, for example, a community-based walking programme supported by digital technology (38).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The rst type focuses on technology learning that is supported by the physical and social environment, for example, a community formed by OA to learn technology from each other at a designated physical meeting point (36). The second type focuses on social interaction that is supported by the physical environment and technology, for instance, a community for sharing, learning and managing music using technology where people can also meet at a designated physical location (37). The third type focuses on physical activity that is supported by the social environment and technology, for example, a community-based walking programme supported by digital technology (38).…”
Section: Resultsmentioning
confidence: 99%
“…The second design consideration is to cultivate a collaborative learning culture in the community, i.e., community members can provide education and training to each other. The study on community music found that enabling competence sharing could support social participation of OA (37). OA in the community radio intervention also expressed that they enjoy sharing and learning experiences with and from each other (49).…”
Section: Co-learningmentioning
confidence: 99%
See 2 more Smart Citations